ARSITEKTUR PERKEBUNAN VERTIKAL SEBAGAI SOLUSI DARI PERMASALAHAN PANGAN DAERAH PERKOTAAN - Alexander Yusuf Yogie (Jurusan Arsitektur dan Perencanaan, 2021)
As population growth continues to increase from time to time, the existing ecology becomes unbalanced caused by human exploitation of existing resources. Architecture that is present in the form of buildings or spaces designed to accommodate human activities is also the reason for the ecological damage that exists on this earth. Architecture that is in favor of ecology is needed to inhibit or even prevent the destruction of nature which will result in the extinction of life in this world. Advanced technology is expected to synergize with architecture. The high demand for food in urban areas and the lack of productive land for food production will become a ticking time bomb that can worsen the situation on earth. Land and water that continue to be exploited to produce food for humans, as well as the carbon footprint that continues to be generated from the production process to the distribution of human food needs in urban areas. The theme beyond ecology (Beyond Ecology) is expected to be the basis for overcoming the problem of food needs in big cities that have minimal productive land. With technology, and the designer's alignment with ecological sustainability can have an impact on food security and reduce the carbon footprint resulting from the distribution and production of food needs in the future. Keywords: Carbon Footprint; Food; Future; Population Growth; Vertical Farming.ABSTRAKSeiring pertumbuhan penduduk yang terus meningkat dari waktu ke waktu membuat ekologi yang ada menjadi tidak seimbang yang disebabkan oleh eksploitasi manusia terhadap sumberdaya yang ada. Arsitektur yang hadir dalam bentuk bangunan atau ruang yang dirancang untuk mewadahi kegiatan beraktivitas manusia turut menjadi alasan kerusakan ekologi yang ada di bumi ini. Arsitektur yang memiliki keberpihakan terhadap ekologi sangat dibutuhkan untuk menghambat atau bahkan mencegah kehancuran alam yang berakibat akan punahnya kehidupan di dunia ini. Teknologi yang maju diharapkan dapat bersinergi dengan arsitektur. Kebutuhan pangan yang tinggi di daerah perkotaan serta minimnya lahan produktif penghasil pangan akan menjadi bom waktu yang dapat memperburuk situasi di muka bumi ini. Tanah dan air yang terus dieksploitasi untuk menghasilkan makanan untuk manusia, serta jejak karbon yang terus dihasilkan dari proses produksi hingga distribusi kebutuhan pangan manusia di perkotaan. Tema melampaui ekologi (Beyond Ecology) ini diharapkan bisa menjadi dasar dalam mengatasi permasalahan kebutuhan pangan di kota besar yang memiliki minim lahan produktif. Dengan teknologi, dan keberpihakan perancang terhadap keberlangsungan ekologi dapat berdampak pada ketahanan pangan serta menurunnya jejak karbon hasil dari distribusi dan produksi kebutuhan pangan di masa depan.